Direct-drive DT implosions with Knudsen number variations. (May 2016) - Kim, Y; Herrmann, H W; Hoffman, N M; Schmitt, M J; Bradley, P A; Gales, S; Horsfield, C J; Rubery, M; Leatherland, A; Johnson, M Gatu; Frenje, J A; Glebov, V Yu
Abstract: Direct-drive implosions of DT-filled plastic-shells have been conducted at the Omega laser facility, measuring nuclear yields while varying Knudsen numbers (i.e., the ratio of mean free path of fusing ions to the length of fuel region) by adjusting both shell thickness (e.g., 7.5, 15, 20, 30 μm) and fill pressure (e.g., 2, 5, 15 atm). The fusion reactivity reduction model showed a stronger effect on yield as the Knudsen number increases (or the shell thickness decreases). The Reduced-Ion-Kinetic (RIK) simulation which includes both fusion reactivity reduction and mix model was necessary to provide a better match between the observed neutron yields and those simulated.